Dampak Komunikasi Siswa Terhadap Hasil Belajar Matematika Sekolah Dasar - Anggraeni, Viana Teti; Sutama, Sutama; Samino, Samino (Universitas Muhammadiyah Surakarta, 2014)
This study aims at know 1) in the contribution learning strategy for achievement; 2) contribution communication math for achievement; 4) the interaction learning strategy shown from the communication math for achievement. This was a quasi-experimental study employing the nonequivalent comparison-group design. This study involved two experimental groups. The sampel comprised Grade V students of SDN I Pengkok consisting of 2 classes to determine the class receiving the treatment of the cooperative learning model of the TGT and the one receiving that of the TTW . The research instruments consisted of test and non-test instruments. The data were analyzed by theunivariate technique, namely the independent sample t-test ata significance level of 5%. The data were analyzed using the three way anova at a significance level of 5%. Follow up by a scheffe test fortwo-tailed test. The results of the study show that; 1) students who taught with TGT get higher achievement; 2) the students who have high math communication competence have better achieve- ment; 4) the students who taught TGT type get higher achievement and the students have high math communication competence get achievement